Acousto-optical receiver of an obstruction passive radar system - Rustamov, Asad; Kerimov, Yashar; Mammedov, Ahmed; Binnatov, Mehman; Katekhliyev, Vusal (Національний технічний університет "Харківський політехнічний інститут", 2023)
The subject of research in the article is the passive radar system of a warship. The purpose of the work was to review the characteristics use of the acousto-optical receiver in the new passive radar system of the warship, to investigate the peculiarities of acoustooptic effect and the relevant synthesis of methods and tools for measuring the photodetector photoelectric characteristics and, in addition, to investigate the energy-and-geometric parameters of laser radiation Justification. It is shown that the transition, impulse and frequency characteristics are taken as the main means to determine the operating and technical parameters of the acousto-optical delay line. It is not possible to unambiguously extrapolate these characteristics to the known models of the characteristics of the acousto-optic radar receiver created on AODL. Research results. In the context of this postulate, mathematical models of the main characteristics of AODL were developed. On the basis of the synchronous compensation pulse obstacles applied to the passive radar acousto-optic receiver on military ships, the full compensation of the obstacles is determined for the effective reception of signals from the acousto-optic receiver. In radar stations (radar), the main attention is focused on the statistical properties of the useful signal and passive obstacles, the speed (frequency) of the signal passing through the passive obstacle and the space-time differences. The recommendations. These features are recommended to be used only in special cases where the target is outside the reflectors for informational duration, amplitude and differences between passive obstacles, obstacle silencing and signal separation. Conclusion. Applying the full attenuation of the band filter and synphase barrier organizers, whose frequency characteristics do not depend on the tuning frequency, it is possible to provide full compensation of obstacles during the effective reception of signals by the acousto-optic receiver in the passive radar system of warships based on the proposed method for high resistance to obstacles, pulse obstacle compensation.

Предметом дослідження в статті є пасивна радіолокаційна система бойового корабля. Метою роботи був огляд характеристик використання акустооптичного приймача в новій пасивній радіолокаційній системі бойового корабля, дослідження особливостей акустооптичного ефекту та відповідний синтез методів і засобів вимірювання фотоелектричних характеристик фотодетектора, а також дослідження енергетично-геометричних параметрів лазерного випромінювання. Обґрунтування. Показано, що основними засобами визначення робочих і технічних параметрів акустооптичної лінії затримки є перехідна, імпульсна та частотна характеристики. Однозначно екстраполювати ці характеристики на відомі моделі характеристик акустооптичного радіолокаційного приймача, створеного на AODL, неможливо. Результати дослідження. У контексті цього постулату були розроблені математичні моделі основних характеристик AODL. На основі синхронної компенсації імпульсних перешкод, застосованих до пасивного радіолокаційного акустооптичного приймача на військових кораблях, визначено повну компенсацію перешкод для ефективного прийому сигналів від акустооптичного приймача. У радіолокаційних станціях основна увага зосереджена на статистичних властивостях корисного сигналу і пасивних перешкод, швидкості (частоті) проходження сигналу через пасивну перешкоду і просторово-часових різницях. Рекомендації. Ці функції рекомендовано використовувати лише в особливих випадках, коли ціль знаходиться за межами відбивачів для тривалості інформації, амплітуди та різниці між пасивними перешкодами, глушінням перешкод і розділенням сигналу. Висновок. Застосовуючи повне ослаблення смугового фільтра та синфазних бар’єрних організаторів, частотні характеристики яких не залежать від частоти налаштування, можна забезпечити повну компенсацію перешкод під час ефективного прийому сигналів акустооптичним приймачем у системі пасивної радіолокації бойових кораблів на основі запропонованого способу високої стійкості до перешкод, імпульсної компенсації перешкод.
Акустооптичний приймач загороджувальної пасивної радіолокаційної системи
Keywords: radar stations; acousto-optical receiver; passive barrier; radio-reflective systems; impulse barriers; band-pass acousto-optical filter; amplitude modulator; радіолокаційні станції; акустооптичний приймач; пасивний бар'єр; радіовідбивні системи; імпульсні бар'єри; смуговий акустооптичний фільтр; амплітудний модулятор